Addition of bevacizumab to preoperative chemotherapy for colorectal liver metastases does not increase perioperative morbidity and mortality - Giakoustidis, Alexandros (Hepat Oncol, 2014)
AIM: Patients with colorectal liver metastases (CRLM) benefit from liver resection. Bevacizumab is commonly used in these patients resulting in a greater number of patients receiving an operation for a potentially curative liver resection, with initially unresectable liver metastases. Our purpose was to evaluate the effect of preoperative bevacizumab administration on perioperative complications in patients undergoing hepatic resection for CRLM. METHODS: A retrospective analysis of patients undergoing hepatic resection for CRLM who received only neoadjuvant chemotherapy (chemotherapy group, n = 133), or neoadjuvant chemotherapy and bevacizumab (chemotherapy and bevacizumab group, n = 103). We compared surgical characteristics, perioperative complications and postoperative liver function. RESULTS: The type of liver resection (minor vs major liver resection) was comparable in the two groups (major liver resection 52.6 vs 62.1%, p = 0.144). The addition of bevacizumab to preoperative chemotherapy does not affect the frequency (chemotherapy group vs chemotherapy and bevacizumab group, 35.3 vs 38.8%, p = 0.581), severity (major complications, 20.3 vs 19.4%, p = 0.487) and type of perioperative complications. Preoperative administration of bevacizumab was associated with a higher peak of postoperative alanine aminotransferase levels but did not affect functional recovery of the liver. CONCLUSION: Neoadjuvant administration of bevacizumab was not associated with an increased risk of postoperative complications after hepatic resection and did not affect the liver's functional recovery. Patients receiving more than eight cycles of bevacizumab are at an increased risk to develop perioperative complications.